2014
DOI: 10.1108/et-04-2013-0057
|View full text |Cite
|
Sign up to set email alerts
|

Chinese students’ participation: the effect of cultural factors

Abstract: Purpose – The purpose of this paper is to provide for Western educators of international Chinese and Confucian Heritage Culture (CHC) students the first integrated review of kiasu, the “fear of missing out”, and its consequences for learning, teaching, and future research. Design/methodology/approach – A review of the economic importance of international Chinese students is provided, followed by consideration of the pedagogical consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 52 publications
3
27
0
Order By: Relevance
“…Much of the research into Chinese students studying abroad has focused on their academic life, with particular attention paid to their levels of participation in class (e.g. Hodkinson and Proropat 2014;Liu 2002), their styles of learning (e.g. Jin andCortazzi 2006, 2011) and more recently their levels of academic attainment in comparison with their peers (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Much of the research into Chinese students studying abroad has focused on their academic life, with particular attention paid to their levels of participation in class (e.g. Hodkinson and Proropat 2014;Liu 2002), their styles of learning (e.g. Jin andCortazzi 2006, 2011) and more recently their levels of academic attainment in comparison with their peers (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This apparent unwillingness to ask questions in class, a behaviour encouraged and expected in western classroom settings, has been discussed previously in literature (Dougherty and Wall, 1991;Hodkinson and Poropat, 2014) who describe the phenomenon of 'Kiasu' where Chinese students are described as being generally less willing to ask questions in class for fear of losing 'face'. Students wish to avoid the embarrassment of providing a wrong answer by asking a question that others already know the answer to, or even stand out too much by answering too many questions correctly.…”
Section: Student-lecturer Communicationmentioning
confidence: 75%
“…According to the research of Chinese students' participation, many Western university professors found the common phenomenon: "silent Chinese student", which explains the fact that the majority of international Chinese students without language confidence usually keep quiet during classes or extracurricular activities. Thus, this behavior impedes the interaction of international Chinese students with their teachers and peers restricting collaboration and limiting their educational achievement (Hodkinson & Poropat, 2014).…”
Section: Attitudes and Values Of Chinese Students In Overseasmentioning
confidence: 99%